WHISTLEBLOWING SYSTEMS AND AUDIT EFFECTIVENESS IN PUBLIC SECTOR GOVERNANCE - Adonia Anita Batkunde; Theresia Febiengry Sitanala (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
This study aims to analyze the role of whistleblowing systems in improving audit effectiveness in public sector governance through a literature review approach. The method used is a literature review, reviewing various scientific sources such as journals, academic books, and institutional reports relevant to the topic. The results of the study indicate that the implementation of effective whistleblowing systems can strengthen the oversight function by providing a secure, anonymous, and reliable channel for reporting violations. This system contributes to early fraud detection, increased transparency, and fostered accountability within public sector organizations. Furthermore, audit effectiveness is also influenced by supporting factors such as whistleblower protection, an ethical organizational culture, and management commitment to follow-up on reports. Therefore, optimal integration of whistleblowing systems can be a strategic instrument in strengthening audit quality and realizing good governance.